The role of serum biomarkers in the decline of cognitive function in hemodialysis patients: a single-center retrospective study - Li, Yulu; Jiang, Riyue; Zhu, Bin; Yu, Jie; Miao, Liying; Shen, Jianqin (Frontiers in Medicine, 2025)
BackgroundCognitive impairment in hemodialysis patients is higher than that in healthy individuals. However, the potential pathogenesis is not fully clear.MethodsIn this retrospective study, 48 maintenance hemodialysis (MHD) patients of our center who participated in cognitive level test 4 years ago were screened by Montreal Cognitive Assessment (MoCA). We then analyzed relationships between the MoCA-derived cognitive level score, demographic, clinical, and laboratory variables.ResultsThe age, dialysis age, Body Mass Index (BMI), and blood calcium levels of MHD patients were significantly abnormal than 4 years ago in this study. Furthermore, we observed that the levels of fibroblast growth factor (FGF-23) in MHD patients with cognitive decline were significantly higher than those in the normal cognitive group. Receiver operating characteristic (ROC) curves demonstrated that FGF-23 was a potential biomarker for diagnosing cognitive decline in hemodialysis patients.ConclusionWe speculate that dialysis age, increased BMI, decreased blood calcium, and the abnormal level of FGF-23 may be independent risk factors for cognitive impairment in hemodialysis patients. Moreover, BMI and decreased blood calcium can be used as predictive factors of hemodialysis-related cognitive impairment.